BILINGUALISM, MULTICULTURAL AND COMPARATIVE LAW IN ENGINEERING EDUCATION - Svetlana V. Barabanova (Высшее образование в России)
This article is devoted to topical problems of bilingual education and formation of multicultural knowledge during the training of a modern engineer. The innovative educational programs of Russian higher schools allow to solve new problems of graduate adaptation to conditions of training and working conditions in the multilingual community.